2021
DOI: 10.1016/j.xjon.2021.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Heart transplant advances: Ex vivo organ-preservation systems

Abstract: Feature Editor Note-In the accompanying article, the team from Duke presents the underlying concepts and early data surrounding the implementation of ex vivo organ preservation in heart transplantation. Cold storage is currently the standard practice in donor-heart preservation, yet with this approach, prolonged ischemic times lead to greater rates of primary graft dysfunction. The goal of ex vivo heart preservation is to minimize ischemic damage during storage, facilitate longer periods of storage, and allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This concept was tested in the EXPAND trial (International Trial to Evaluate the Safety and Effectiveness of The Portable Organ Care System Heart For Preserving and Assessing Expanded Criteria Donor Hearts for Transplantation), which analyzed high-risk transplants with anticipated prolonged ischemic times (>4 h) or marginal donor heart features (left ventricular hypertrophy, an ejection fraction of 40-50%, donor downtime >20 min, and donor age >55 years). The short-term results showed excellent short-term outcomes in 75 patients transplanted from a total of 93 hearts recovered and perfused on the OCS [34].…”
Section: Clinical Studies With the Organ Care Systemmentioning
confidence: 94%
See 1 more Smart Citation
“…This concept was tested in the EXPAND trial (International Trial to Evaluate the Safety and Effectiveness of The Portable Organ Care System Heart For Preserving and Assessing Expanded Criteria Donor Hearts for Transplantation), which analyzed high-risk transplants with anticipated prolonged ischemic times (>4 h) or marginal donor heart features (left ventricular hypertrophy, an ejection fraction of 40-50%, donor downtime >20 min, and donor age >55 years). The short-term results showed excellent short-term outcomes in 75 patients transplanted from a total of 93 hearts recovered and perfused on the OCS [34].…”
Section: Clinical Studies With the Organ Care Systemmentioning
confidence: 94%
“…Furthermore, MP allows for donor heart assessment before implantation, and this may facilitate the use of marginal donors. More importantly, MP may become a platform for cardioprotective approaches, enabling the repair and reconditioning of donor hearts [34]. In heart transplantation, two methods of ex vivo perfusion have been reported: hypothermic (4-8 • C) and near normothermic (>32.8 • C).…”
Section: Ex Vivo Machine Perfusion As a Novel Strategy To Preserve Th...mentioning
confidence: 99%
“…The study demonstrated short-term survival rates were 94.7 and 88% at 30 days and 6 months respectively. The incidence of primary graft dysfunction at 24 hours postoperatively was 10.7% [2,20,53,54].…”
Section: Author Detailsmentioning
confidence: 95%
“…Preparation and management of heart on Organ Care System The heart is prepared for OCS on the back table [73]: (1) Insertion of aortic cannula; an appropriately sized aortic tip cannula is attached to the ascending aorta using a cable tie. This serves as the point of suspension for the heart on the device and provides the route for the delivery of perfusate.…”
Section: Operative Techniquementioning
confidence: 99%